Inference of Process Capability Index Cpy for 3-Burr-XII Distribution Based on Progressive Type-II Censoring - Rashad M. EL-Sagheer; Mustafa M. Hasaballah (International Journal of Mathematics and Mathematical Sciences)
In this paper, we discussed the estimation of the index Cpy for a 3-Burr-XII distribution based on Progressive Type-II censoring. The maximum likelihood and Bayes method have been used to obtain the estimating of the index Cpy. The Fisher information matrix has been used to construct approximate confidence intervals. Also, bootstrap confidence intervals (CIs) of the estimators have been obtained. The Bayesian estimates for the index Cpy have been obtained by the Markov Chain Monte Carlo method. Also, the credible intervals are constructed by using MCMC samples. Two real-datasets have been discussed using the proposed index.